Cranial MR Imaging Findings of Potassium Chlorate Intoxication - Mutlu, Hakan; Silit, Emir; Pekkafali, Zekai; Basekim, C. Cinar; Kizilkaya, Esref; Ay, Hakan; Karsli, A. Fevzi (American Journal of Neuroradiology, 2003)
Summary: We present the case of a patient who attempted suicide by ingesting matchstick heads (55% potassium chlorate). The patient presented to the emergency room with loss of consciousness, and MR imaging revealed symmetric hyperintense signal within the deep gray matter and medial temporal lobes. The patient improved after undergoing conventional treatment and hyperbaric oxygen.